Could the gut microbiota community in the coral trout Plectropomus leopardus (Lacepède, 1802) be affected by antibiotic bath administration?. Issue 3 (19th April 2020) - Zheng, Xing; Zhou, Shengjie; Hu, Jing; Yang, Rui; Gu, Zhifeng; Qin, Jian G.; Ma, Zhenhua; Yu, Gang
Abstract: Gut microbiota in fish plays an important role in the nutrient digestion, immune responses and disease resistance. To understand the effect of fluoroquinolone antibiotic bath administration on fish gut microbiota, the gut microbiota community in the coral trout Plectropomus leopardus (Lacepède, 1802) was studied after enrofloxacin bathing treatment at two concentrations (5 and 10 mg/L) and 0 mg/L as control. A total of 90 fish were used in this study, and three replicates were used for each treatment. After a 24‐hr bath, the gut bacterial composition was analyzed using high‐throughput Illumina sequencing. The results indicated that the richness, diversity and the dominant bacterial taxa of P. leopardus gut bacteria were not affected by enrofloxacin bathing ( p > .05). Proteobacteria and Firmicutes were the dominant phyla, and Exiguobacterium, Citrobacter, Vibrio, Acinetobacter, Pseudomonas were the dominant genus. The findings in the present study provide an understanding on the relationship between fish gut bacteria community and antibiotic bath administration. The findings of this study are instructive on the antibiotic bath administration applied for the management of P. leopardus health in aquaculture. Abstract : The gut microbiota community in the coral trout Plectropomus leopardus (Lacepède, 1802) was studied after enrofloxacin bathing treatment at two concentrations (5 and 10 mg/L) and 0 mg/L as control. After a 24‐hr bath, the gut bacterial composition was analyzed using high‐throughput Illumina sequencing. The results indicated that the richness, diversity and the dominant bacterial taxa of P. leopardus gut bacteria were not affected by enrofloxacin bathing ( p > .05).